2017
DOI: 10.3390/app7101063
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Guided Wave Propagation in Wood Utility Poles: Finite Element Modelling and Parametric Sensitivity Analysis

Abstract: Abstract:Recently, guided wave (GW)-based non-destructive evaluation (NDE) techniques have been developed and considered as a potential candidate for integrity assessment of wood structures, such as wood utility poles. However, due to the lack of understanding on wave propagation in such structures, especially under the effect of surroundings such as soil, current GW-based NDE methods fail to properly account for the propagation of GWs and to contribute reliable and correct results. To solve this critical issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Because of this, they could investigate the characteristics of the propagation of harmonic waves. Yu and Yan [25] conducted a computer analysis of the wave propagation behavior in wood poles by using a technique known as the FEM. They observed that a hardwood pole with a stronger longitudinal elastic modulus always showed more directed wave behavior, and they empirically demonstrated that their findings were correct.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, they could investigate the characteristics of the propagation of harmonic waves. Yu and Yan [25] conducted a computer analysis of the wave propagation behavior in wood poles by using a technique known as the FEM. They observed that a hardwood pole with a stronger longitudinal elastic modulus always showed more directed wave behavior, and they empirically demonstrated that their findings were correct.…”
Section: Introductionmentioning
confidence: 99%